Synthesis, Identification and Screened anti-microbial activity of some new N-substituted quinazoline-4-one, oxazine-4-one and thiazine-4-one derivatives bearing a 4(3H)-quinazolinone moiety - Saeed, Noor Nashaat; Al-Majidi, Suaad M. H. (Iraqi Journal of Science, 2026)
This work includes synthesis of new heterocyclic derivatives of quinazoline-4-one, oxazine-4-one and thiazine-4-one and studying their application as anti-microbial. The preparation process commenced with the reaction of para methoxybenzoyl chloride with anthranilic acid to give 2-(4-methoxy benzamido) benzoic acid (compound 1). This compound then reacts with acetic anhydride under dry conditions, resulting in the formation of benzoxazinone compound 2. Following this, compound 2 undergoes a reaction with ethyl glycinate hydrochloride under basic conditions, yielding in compound 3 serves as the starting material for the synthesis of some heterocyclic compounds by reaction with nitrogen nucleophiles. The nucleophilic addition of 80% hydrazine hydrate to compound 3 yields the corresponding hydrazide 4. Subsequently, the condensation of compound 4 with various para-substituted aromatic aldehydes in the presence of glacial acetic acid leads to the synthesis of Schiff base derivatives 5-9.  Finally, the compound 5-9. These compounds (5-9) can undergo three distinct reactions. The first reaction involves treating compounds 5-9 with anthranilic acid to obtain 1,4 dihdroquinazoline -4- one 10-14. The second reaction entails reacting compounds 5-9 with salicylic acid to obtain oxazine-4-one 15-19. The third reaction involves the interaction of compounds 5-9 with 2-mercapto benzoic acid to obtain thiazine -4-one 20-24. The newly synthesized compounds were characterized via spectral techniques; their [ FT-IR, 1H-NMR and 13C-NMR]. Additionally, we evaluated the antibacterial effects of some synthesized compounds against Grame-negative Escherichia coli, Pseudomonas aeruginosa, Grame-positive bacteria Staphylococcus, and Bacillus cereus and two kinds of fungi Candida albicans and Rhizopus microrhizosporium. The result showed that some of the compounds were very effective against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus, and Bacillus cereus. Furthermore, strong activity is observed in Rhizopus microrhizosporium and Candida albicans. On the other hand, some of the compounds were effective against Candida albicans and Rhizopus microrhizosporium and not effective against all strains of bacteria: Escherichia coli, Pseudomonas aeruginosa, Staphylococcus, and Bacillus cereu